Bond On Set - Williams, Greg (London DK Publisher, 2006)
"Bond on Set -- Casino Royale provides a fascinating documentary celebrating the skills, the sheer hard work, and the magic that combine to create the unforettable world of James Bond, 007"--Jacket.
Include Color Illustration
Keywords: Casino Royale (Motion picture : 2006) -- Motion pictures -- Great Britain